INTEGRITY WHISTLEBLOWERS IN THE ROMANIAN LEGAL SYSTEM - Florin STOICA (Challenges of the Knowledge Society)
Illegal activities and abusive practices can occur in any organisation, public or private, small or large. They can take many forms, such as corruption or fraud, unfair business practices or negligence. If no action is taken, they may cause serious damage to the public interest. A law itself gives the appearance of a safety instrument for situations in which an official public or contract employee intends to refuse the execution of an order that he considers illegal. Although this provision is theoretically included in the legislation, any employee who does not fulfils an order outside of legality was subject to a series of unsustainable behaviors that resulted in removal or withdrawal from the system. At this moment, in the Romanian landscape, we lack a culture of integrity whistleblowers, and those who find the strength to report they are seen rather as an exception and idealised as heroes of the system. Perhaps we could rather say that there is a culture strongly marked by the traumas of the past in terms of reporting. Starting from the culture of the country which, at the moment, discourages integrity whistleblowers, we note that, just as in the European directive that we were obliged to transpose, this proposed law encourages and prioritises internal reporting. We can understand the reasons behind this encouragement, however, in the Romanian context, we believe that the prioritisation of internal reporting can and must be corroborated with subsequent instrumentation actions a anonymous reports. Seen as a measure that comes to consecrate the modernism of the Romanian legal system, but also as a measure of the legislative maturity it has reached after countless reforms, the initiation of investigations regarding integrity whistleblowers has become a reality. What will be the impact on Romanian society? How will they integrate into the judicial system? What will be the value as proof?